The Creation of the World in Jewish Esoteric Philosophy - De Souza, Igor H. (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2021)
A discussion of Création du monde et limites du langage. Sur l’art d’écrire des philosophes juifs médiévaux by David Lemler.